Degradation of Methyl Parathion by a Soil Bacterial Isolate: A Pot study - Mishra, Archana; Khan, Jamaluddin; Pandey, A. K. (Journal of Experimental Sciences)
The indiscriminate use Â of chemicals fertilizers and pesticides have not only deteriorated Â Â the environment but also the groundwater resources as well .Their intensive consumption Â Â causesÂ Â deleterious effects on plant, animal and aquatic ecosystems thereby causing serious problems related to health. Â Â Since these Â are one of theÂ factors Â which are Â responsible for Â the contamination of air, water and terrestrial ecosystems and also Â the cause of Â Â disruption of biogeochemical cycling, Â it is extremely important to bring down ,the toxicity Â levels Â that these chemicals impose on the environment, by the use of effective technology, which Â is Â Â Â cost effective and safe. It has been suggested that biodegradation becomes an attractive option for destruction of pesticides since it utilizes a natural process and offers the potential for being cost effective as well as safe technology Thus the present study deals with the isolation and Â Â use indigenous bacteria for degradation ofÂ an organophosphorous pesticide- methyl parathion Â present in the soil samples which were collected from the pesticide contaminated agricultural field.